Real-World Evidence for the Safety and Efficacy of CGRP Monoclonal Antibody Therapy Added to OnabotulinumtoxinA Treatment for Migraine Prevention in Adult Patients With Chronic Migraine - Mechtler, Laszlo; Saikali, Nicolas; McVige, Jennifer; Hughes, Olivia; Traut, Alexandra; Adams, Aubrey Manack (Frontiers in Neurology, 2022)
Background: OnabotulinumtoxinA and calcitonin gene-related peptide (CGRP) monoclonal antibodies (mAbs) target different migraine pathways, therefore, combination treatment may provide additional effectiveness for the preventive treatment of chronic migraine (CM) than either treatment alone. The objective of this study was to collect real-world data to improve the understanding of the safety, tolerability, and effectiveness of adding a CGRP mAb to onabotulinumtoxinA treatment for the preventive treatment of CM. Methods: This was a retrospective, longitudinal study conducted using data extracted from a single clinical site's electronic medical records (EMR) of adult patients (≥18 years) with CM treated with ≥2 consecutive cycles of onabotulinumtoxinA before ≥1 month of continuous onabotulinumtoxinA and CGRP mAb (erenumab, fremanezumab, or galcanezumab) combination treatment. Safety was evaluated by the rate of adverse events (AE) and serious adverse events (SAE). The proportion of patients who discontinued either onabotulinumtoxinA, a CGRP mAb, or combination treatment, and the reason for discontinuation, if available, was collected. The effectiveness of combination preventive treatment was assessed by the reduction in monthly headache days (MHD). Outcome data were extracted from EMR at the first CGRP mAb prescription (index) and up to four assessments at 3, 6, 9, and 12 months post-index. The final analyses were based on measures consistently reported in the EMR. Results: EMR were collected for 192 patients, of which 148 met eligibility criteria and were included for analysis. Erenumab was prescribed to 56.7% of patients, fremanezumab to 42.6%, and galcanezumab to 0.7%. Mean (standard deviation [SD]) MHD were 20.4 (6.6) prior to onabotulinumtoxinA treatment and 14.0 (6.9) prior to the addition of a CGRP mAb (baseline). After real-world addition of a CGRP mAb, there were significant reductions in MHD at the first assessment ( 3 months) (mean −2.6 days/month, 95% CI −3.7, −1.4) and at all subsequent visits. After 12 months of continuous combination treatment, MHD were reduced by 4.6 days/month (95% CI −6.7, −2.5) and 34.9% of patients achieved ≥50% MHD reduction from index. AEs were reported by 18 patients (12.2%), with the most common being constipation (n = 8, 5.4% [onabotulinumtoxinA plus erenumab only]) and injection site reactions (n = 5, 3.4%). No SAEs were reported. Overall, 90 patients (60.8%) discontinued one or both treatments. The most common reason for discontinuing either treatment was lack of insurance coverage (40%); few ( 14%) patients discontinued a CGRP mAb and none discontinued onabotulinumtoxinA due to safety/tolerability. Conclusion: In this real-world study, onabotulinumtoxinA was effective at reducing MHD and the addition of a CGRP mAb was safe, well-tolerated and associated with incremental and clinically meaningful reductions in MHD for those who stayed on the combination treatment. No new safety signals were identified. Of those who discontinued, the majority reported lack of insurance coverage as a reason. Prospective real-world and controlled trials are needed to further evaluate the safety and potential benefits of this combination treatment paradigm for people with CM.